2017
DOI: 10.1186/s13104-017-3032-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-rafts remain stable even after ionizing radiation induced disintegration of β1 integrin containing focal adhesions

Abstract: ObjectiveAdhesion of cells to the extracellular matrix is facilitated by integrin receptors. We recently found that a nanoscale organization of plasma membrane located integrins containing the β1 subunit is responsible for an enhanced radio-resistance in 3D cultured cells over cells grown in 2D. While ionizing radiation is known to have broad effects on the lipid composition of the plasma membrane and their organization in lipid-rafts, it is not clear whether the effects of ionizing radiation on the nanoscale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…At the same time, the biochemical properties of RFs are similar to migrasome, which are rich in Actin and are lipid microdomains (Ma et al, 2015, Wu et al, 2017. Because the important concomitant ingrigrins of migrasome is also an important component of lipid microdomain (Babel et al, 2017). In summary, we believe that RFs have a very high similarity to migrasome.…”
Section: Plant Plasmodesmata and Animal Migrasomementioning
confidence: 64%
“…At the same time, the biochemical properties of RFs are similar to migrasome, which are rich in Actin and are lipid microdomains (Ma et al, 2015, Wu et al, 2017. Because the important concomitant ingrigrins of migrasome is also an important component of lipid microdomain (Babel et al, 2017). In summary, we believe that RFs have a very high similarity to migrasome.…”
Section: Plant Plasmodesmata and Animal Migrasomementioning
confidence: 64%
“…Further, a synthetic bile acid-phospholipid conjugate that inhibits integrin causes integrin internalization via lipid rafts [ 106 ]. Indeed, integrin β1 colocalizes with cholesterol in lipid rafts while ionizing radiation separates integrin β1 from cholesterol rafts [ 107 ]. Clearly, integrin adhesion and signaling correlates with the recruitment of these membrane proteins to lipid rafts.…”
Section: The Role Of Cholesterolmentioning
confidence: 99%
“…Some studies have demonstrated the role that lipid rafts play in radiotherapy resistance. A recent study has shown that the integrity of lipid rafts remains steady, even after radiation exposure [6]. Another recent study illustrates that radiation can enhance the integrity of lipid rafts in lung cancer cells, which might contribute to the development of radiation resistance [7].…”
Section: Introductionmentioning
confidence: 99%